Microzooplankton communities and their grazing of phytoplankton under artificial upwelling in the oligotrophic ocean - Spilling, Kristian; Arellano San Martín, Mirian; Granlund, Mira; Schulz, Kai G.; Spisla, Carsten; Vanharanta, Mari; Goldenberg, Silvan Urs; Riebesell, Ulf (Frontiers in Marine Science, 2023)
Ocean artificial upwelling has been suggested to boost primary production and increase harvestable resources such as fish. Yet, for this ecosystem-based approach to work, an effective energy transfer up the food web is required. Here, we studied the trophic role of microzooplankton under artificial upwelling via biomass and community composition as well as grazing rates on phytoplankton. Using mesocosms in the oligotrophic ocean, we supplied nutrient-rich deep water at varying intensities (low to high) and addition modes (a Singular large pulse or smaller Recurring pulses). Deep-water fertilization created a diatom-dominated bloom that scaled with the amount of inorganic nutrients added, but also Synechococcus-like cells, picoeukaryotes and nanophytoplankton increased in abundance with added nutrients. After 30 days, towards the end of the experiment, coccolithophores bloomed under recurring upwelling of high intensity. Across all upwelling scenarios, the microzooplankton community was dominated by ciliates, dinoflagellates (mixo- and heterotrophic) and radiolarians. Under the highest upwelling intensity, the average grazing rates of Synechococcus-like cells, picoeukaryotes and nanophytoplankton by microzooplankton were 0.35 d-1 ± 0.18 (SD), 0.09 d-1 ± 0.12 (SD), and 0.11 d-1 ± 0.13 (SD), respectively. There was little temporal variation in grazing of nanophytoplankton but grazing of Synechococcus-like cells and picoeukaryotes were more variable. There were positive correlations between abundance of these groups and grazing rates, suggesting a response in the microzooplankton community to prey availability. The average phytoplankton to microzooplankton ratio (biovolume) increased with added deep water, and this increase was highest in the Singular treatment, reaching 30 (m3 m-3), whereas the phytoplankton to total zooplankton biomass ratio (weight) increased from 1 under low upwelling to 6 (g g-1) in the highest upwelling but without a difference between the Singular and the Recurring mode. Several smaller, recurring upwelling events increased the importance of microzooplankton compared with one large pulse of deep water. Our results demonstrate that microzooplankton would be an important component for trophic transfer if artificial upwelling would be carried out at scale in the oligotrophic ocean.